Distribution of Lead and Cadmium in Soils on Koko Seaport, Delta State, Nigeria - A. Michael; P. N. Okeke; C. E. Ihejirika; C. C. Ejiogu (Journal of Applied Sciences and Environmental Management, 2023)
Soil contamination by Lead and Cadmium is a prevalent ecological problem that requires attention because these two metals are toxic and could accumulate and translocate in soil over time, which poses a risk of entering the food chain and affecting the living organisms in the food web. The objective of this study is to evaluate the levels of Pb and Cd in soil from selected sampling locations of the Koko Seaport in Delta State, Nigeria. Five areas near Koko Seaport were investigated for the transport of these heavy metals in the soil. Statistical analysis using ANOVA and chart models was used to determine the concentration of these metals. Cadmium and lead levels that were significant were found in the studied areas. The data did not show any differences between the two metals due to the significance of the *p>0.05 value. The variations showed a surge in comparisons of the amounts of cadmium in stations 2 and 3, respectively, as well as significant values for cadmium compared to lead. The outcome was directly influenced by the type and quantity of hazardous wastes present in the research area. The recommended remedial actions for these metals include soil cleansing, immobilization, and the choice of plants with hyper bio accumulation for phytoremediation methods that allow the use of genetic engineering.